Competency and Career Path of Nurses in Thai Correctional System: Opportunities for Development - Sawasdipanich, Nantaga; Puektes, Supa; Kongpromsuk, Vichuda; Chewchuapun, Kanokwan (Journal of Thailand Nursing and Midwifery Council, 2021)
A prison is a community of a large number of inmates many of whom suffer health problems ranging from underlying diseases to diseases acquired during imprisonment. This condition necessitates multi-dimensional healthcare, including health promotion, disease prevention, medical treatment, and rehabilitation. Because nurses operating in a correctional facility play a signifcant part in providing healthcare services for the inmates, these nurses are expected to possess task-specifc, in addition to principal and general professional, competency. These nurses are also expected to possess legal and ethical understanding, along with skills in coordinating with offcials from other correctional divisions to arrange proper healthcare services for the inmates. Correctional facility nurses, therefore, should be trained to enhance their specifc competency in response to their role in providing healthcare services for inmates who have complicated health problems and are confned to a more disease-prone environment than are ordinary people. Also, a career path for correctional facility nurses should be more clearly defined. This article discusses issues related to the working condition of correctional facility nurses, their required areas of competency, and their career path. The recommendations offered, which are applicable to the policymaking, organisational, and individual levels, are concerned with the direction of developing correctional facility nurses’ competency and career path, to optimise their potential, lift their morale, and increase their motivation to continue serving in correctional facilities.